Molecular detection and phylogenetic analysis of Orf viruses from goats in Jiangxi province, China - Zhang, Zhibang; Zhang, Xiaoyan; Meng, Ping; Feng, Kang; Gong, Jinxiang; Yang, Ziyin; Yang, Taotao; Xu, Xingli; Zheng, Wenya; Li, Pengcheng (Frontiers in Veterinary Science, 2024)
Orf is a zoonosis caused by the Orf virus (ORFV), which is endemic in goats, sheep, and wild ruminants worldwide. Orf infection is prevalent in China, with outbreaks reported in several provinces. Currently, there is limited information available regarding the characterization of ORFV strains in Jiangxi province. This study investigated an acute outbreak of Orf that occurred in 2021 in a goat herd in the Jiangxi province of China. Clinical signs in this case included lesions on the lips, nose, and inside the mouth. The presence of ORFV was confirmed from tissue samples by polymerase chain reaction (PCR). The nucleotide sequences of the B2L and F1L genes were fully sequenced and used to construct phylogenetic trees. The results of this investigation identified the ORFV JXxy2021 as the cause of the outbreak. The phylogenetic analysis revealed that the ORFV strain JXxy2021 had the highest similarity to the ORFV strains GO and FJ-SL from the neighboring province of Fujian. This suggests that JXxy2021 was likely transmitted from Fujian province. The results have provided valuable information on the genetic characteristics of JXxy2021 and the endemic situations of Orf in China.